(untitled) (Homoeopathy for All, 2024)
Haemolacria is an exceedingly rare condition. Due to low incidence and limited literature, the prevalence and predilection of haemolacria for a specific gender, race, or age is not known. The pathophysiology of haemolacria depends on the case-specific cause of this condition. Homoeopathy can help in haemolacria, it is evident from this case of a girl age 11 years who was suffering from haemolacria and treated with in 1year with Homoeopathic similimum which was selected on the basis of individualisation.